Sosialisasi Pemanfaatan Media Sosial Sebagai Media Promosi Serta Penyebaran Informasi di Desa Dalang - I Made Arya Budhi Saputra; I Made Bhaskara Gautama; I Gusti Ayu Pramitaresthi; K. Putri Setyaningrum; Kadek Ayu Widyawati; Ni Komang Ayu Trinadi; Ni Luh Putu Satya Devi; Putu Muliana Putra; I Gusti Ngurah Alit Bayu Bramanta; Ni Putu Gita Meilyanjani; I Komang Wira Adhityasaputra; IGKG Puritan Wijaya ADH; I Gusti Ngurah Wikranta Arsa (Journal of Community Development, 2022)
COVID-19 has had a major impact on all sectors of society, starting from health, the economy, and tourism. The outbreak of the spread of this disease causes a lack of public awareness of the importance of clean and healthy living behavior (PHBS). PHBS is an effort that can be made by the community to improve the quality of health through individuals, groups, or society at large. As well as the restrictions on community activities, especially in the economic sector, the people's purchasing power decreases for MSME products, precisely in Dalang Village. Therefore, in this community service, UKM KSR-PMI Unit ITB STIKOM Bali held community service in the form of health socialization and socialization of the use of technology. Broadly speaking, this activity is divided into health socialization which aims to increase public awareness of the importance of maintaining a Clean and Healthy Lifestyle (PHBS) and socialization of the use of social media technology and e-commerce which aims to improve and help the economy and MSMEs in Dalang Village. . This activity that has been carried out by UKM KSR-PMI Unit ITB STIKOM Bali has a fairly large and good impact on people's understanding which can be seen from the results of the percentage of questionnaires. From this activity 88% showed that participants had understood the socialization material that had been given directly.